Morphometric Evaluations and Yields from Commercial Cuts of Black Pacu Colossoma macropomum (Cuvier, 1818) in Different Body Weights - Jucilene Cavali; Beatriz Andrade Nóbrega; Jerônimo Vieira Dantas Filho; Elvino Ferreira; Marlos Oliveira Porto; Rute Bianchini Pontuschka; Rilke Tadeu Fonseca de Freitas (The Scientific World Journal)
For the Amazon, it is important to encourage the production of native fish, since there are several species of zootechnical interest. For this, it is necessary to know the species since its acquisition, production, processing, and marketing. Therefore, the aim of this study was to analyze the yield, correlations, and profitability of different cuts of black pacu (Colossoma macropomum) in five weight categories. Data from 220 black pacus were obtained, with a weight range of 2725 ± 1975 g. Yields of commercial cuts and morphometric measurements were evaluated in five weight classes. Kruskal–Wallis test (α = 0.05) was used to compare the average income. And, to verify the correlation between the morphometric measures and the yields, Spearman’s correlation was performed (α = 0.05). To obtain the profit of the weight classes due to the cut produced, an economic analysis was carried out considering the cost of buying the fish. Yields of fillet, ribs, and steak were higher in classes 3 and 4, while in the same classes, the yield of residues was the lowest. Despite classes 1, 2, and 5 showing lower yields, the economic analysis presented that the production of fillet and ribs was profitable. The measures of total length and standard length have a high positive correlation with the yield of meat in all classes, as well as the average circumference and caudal circumference in classes 1, 2, and 4, which can be used to determine the yields of this commercial cut.